Food Safety: Cook It Safely! - Jennifer Hillan; Linda B. Bobroff (EDIS)
Do you know the minimum safe internal temperatures for foods? Refer to this revised 1-page fact sheet written by Jennifer Hillan and Linda B. Bobroff, and published by the UF Department of Family, Youth and Community Sciences, October 2011.